DESAIN PENGAJARAN BAHASA BERBASIS TUGAS: SYSTEMATIC LITERATURE REVIEW - Mantasiah R; Fathullah Wajdi; Jafar Jafar (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to map the characteristics of task-based language teaching (TBLT) design, the patterns of interaction it facilitates, its contribution to language learning improvement, and the supporting and inhibiting factors in its implementation. The research employed a systematic literature review method with the PRISMA protocol, a mixed-method convergent integrated review design, and narrative-thematic synthesis of 16 empirical articles selected from Scopus, ERIC, and ScienceDirect. The results indicate that effective TBLT design is characterised by meaning-oriented tasks, collaborative work, authentic topics, teacher scaffolding, multimodal resources, and proportional integration of technology. The most dominant interaction pattern is learner–learner, while improvement in language learning appears in the linguistic, communicative, and affective domains. It is concluded that the success of TBLT is determined more by the quality